US security policy and South America after September 11: A Brazilian perspective - Rochman, Alexandre Ratner [UNESP] (My University, 2006)
The terrorist attacks of 9 Ill profoundly affected the international system, not only because of the tragic deaths and the impact on the world economy, but also because of the wide range of insecurities they revealed in every country around the world. The international community learned a lesson from the events of 9/11. Since terrorism is by nature transnational, it must be fought in a coordinated manner. No region can be left aside in this effort.